Multidimensional difference analysis in gastric cancer patients between high and low latitude - Wang, Liqiang; Cai, Mengdi; Song, Ying; Bai, Jing; Sun, Wenjing; Yu, Jingcui; Du, Shuomeng; Lu, Jianping; Fu, Songbin (Frontiers in Genetics, 2022)
Genetic variation has been shown to affect tumor growth and progression, and the temperature at different latitudes may promote genetic variants evolution. Geographical data with latitudinal information is of importance to understand the interplay between genetic variants and environmental influence, such as the temperature, in gastric cancer (GC). In this study, we classified the GC samples from The Cancer Genome Atlas (TCGA) database into two groups based on the latitudinal information of patients, and found that GC samples with low latitude had better clinical outcome. Further analysis revealed significant differences in other clinical factors such as disease stage and grade between high and low latitudes GC samples. Then, we analyzed the genomic and transcriptomic difference between two groups. Furthermore, we evaluated the activity score of metabolic pathways and infiltrating immune cells in GC samples with different latitudes using ssGSEA algorithm. These results showed that GC samples at low latitude had lower tumor mutational burden and subclones as well as higher DNA repair activities. Meanwhile, we found that most immune cells were associated with the prognosis of low latitude GC patients. Finally, we constructed and validated an immune related prognostic model to evaluate the prognosis of GC samples at different latitudes. This study has provided a further understanding of the geographical contribution to GC at multi-omic level, and may benefit the individualized treatment of GC patients at different latitudes.